2021
DOI: 10.2147/cmar.s308659
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Pretreatment Fibrinogen-to-Lymphocyte Percentage Ratio Predict Tumor Staging and Poor Survival in Non-Small Cell Lung Cancer Patients with Chemotherapy or Surgery Combined with Chemotherapy

Abstract: Purpose The objective of our study was to assess the association between lymphocyte percentage (LY%), fibrinogen (FIB), fibrinogen-to-lymphocyte percentage ratio (FLR) and the tumor staging and the clinical outcome role in non-small cell lung cancer (NSCLC) patients with chemotherapy or surgery combined with chemotherapy. Patients and Methods Between August 2013 and October 2020, 375 patients initially diagnosed with NSCLC and 201 healthy subjects were enrolled in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…showed worse OS and DFS in patients with esophageal squamous cell carcinoma after radical esophagectomy with elevated preoperative FLR. Similarly, poorer OS was observed in non-small cell lung cancer patients with high FLR in a study of Liu et al [18]. The negative prognostic value of FLR was even shown in patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…showed worse OS and DFS in patients with esophageal squamous cell carcinoma after radical esophagectomy with elevated preoperative FLR. Similarly, poorer OS was observed in non-small cell lung cancer patients with high FLR in a study of Liu et al [18]. The negative prognostic value of FLR was even shown in patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 68%
“…Based on three prior studies, showing the prognostic significance of FLR in esophageal [16], gastric [17], and non-small lung cancer [18], we wanted to examine the role of FLR in ACC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is notable that reports regarding the role of LFR in cancer are still scarce, with only a few relevant studies but only with some relevant studies. For example, Liu et al included 375 stages 1–4 non-small cell lung cancer patients and explored the prognostic role of the FIB-to-lymphocyte percentage ratio (FLpR), and the results indicated that patients with a high FLpR would have an increased risk of death [ 46 ]. In addition, Huang et al indicated that a high FIB to LC ratio (FLR) correlated with peritoneal dissemination in gastric cancer [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocytes are important antineoplastic factors, which play a significant role in cancer-specific immune response ( 14 ). Recently, a novel prognosticator fibrinogen-to-lymphocyte ratio (FLR) has been proposed, which has been proved to evaluate the prognosis in gastric cancer ( 15 ), esophageal cancer ( 16 ), non-small cell lung cancer ( 17 ) and head and neck adenoid-cystic carcinoma ( 18 ). However, there is no study on the predictive performance of NLR and FLR in CRA recurrence.…”
Section: Introductionmentioning
confidence: 99%